ANALYSIS OF YOUTUBE VIDEOS ADDRESSING THE INDWELLING URINARY CATHETERIZATION PROCEDURE IN WOMEN - Anna Patrícia Cavalcante de Morais Pinto; Marta Silvanêre Pereira Dantas; Pétala Tuani Candido de Oliveira Salvador; Cláudia Cristiane Filgueira Martins Rodrigues; Viviane Euzébia Pereira Santos (Universidade Federal do Paraná, 2015)
This is a descriptive research with a quantitative approach, carried out on the website YouTube to characterize YouTube videos addressing the indwelling urinary catheterization procedure in women. A search of the videos was carried out in September 2014 using the descriptor "urinary catheterization". Twenty-nine videos were analyzed, only three of which were in accordance with the standards established in the literature; among the main errors found, the absence of registration in the medical records, hand washing and use of the same glove for antisepsis and catheter insertion are highlighted. Even though YouTube is currently a widespread tool, there is a lack of videos reproducing the procedure according to literature recommendation, which can negatively influence the population that uses it to correct their knowledge.